2001
DOI: 10.1046/j.1365-3016.2001.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative impact of early maternal marital age during the childbearing period

Abstract: Early marriage of girls, close to age of menarche, is a widespread practice in Arab countries. Knowledge on the cumulative effect of early maternal marriage on maternal and infant health during the childbearing period is insufficient. The objectives of this study were to estimate the prevalence of early maternal marriage in Jeddah, identify its relation with other maternal risk factors, and investigate the cumulative impact of early maternal marriage on subsequent maternal health and pregnancy outcomes through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Older‐age childbearing and multiparity were shown from our results to increase the risk of having an auditory, visually and mentally disabled child. Also, high parity and thus old‐age pregnancies are typical for the Middle East region as documented in several studies 11, 13–16 …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Older‐age childbearing and multiparity were shown from our results to increase the risk of having an auditory, visually and mentally disabled child. Also, high parity and thus old‐age pregnancies are typical for the Middle East region as documented in several studies 11, 13–16 …”
Section: Discussionmentioning
confidence: 86%
“…Early childbearing was shown from our results to increase the risk of having an auditory disabled child. Arab countries as a whole are known to have high rates of early maternal marriage, a practice related to traditions and beliefs 11–13 . It is true that early marriage and childbearing save the population from many health hazards but an age limit for the marriages and consequently childbearing should be decided, taking into account the biological maturity of females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with higher education are more likely to know the long-term benefits of the utilization of services compared with women with less education or uneducated women. Educated mothers are more likely to take advantage of public health care services (Shawky & Milaat, 2001), seek high-quality services and have greater ability to use health care inputs that offer improved care than women with no education (Celik & Hotchkiss, 2000). Education may impart feelings of self-worth and self-confidence to women, which some have argued are more important in bringing about changes in health-related behaviour than exposure to relevant information (Chanana, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to note the sharp decline in adolescent births (see Table 2) in the UAE. Shawky and Milaat (2001) found that in Saudi Arabia, 9.8% of women currently give birth before their 16th birthday. Their findings showed that women who gave birth before age 16 years were at double the risk of developing chronic diseases and experiencing miscarriages, stillbirths and infant deaths throughout their childbearing years.…”
Section: Discussionmentioning
confidence: 99%